Morinda officinalis oligosaccharides attenuate mitochondria-associated ferroptosis via the NOX4/mitoGPX4 pathway in myocardial ischemia‒reperfusion injury - Chen, Yuqiong; Tian, Yuan; Guan, Bo; Chang, Yiling; Yan, Xiaopei; Song, Qi; Chen, Wenting; Chen, Lin; Li, Wei; Mao, Wenjun; Zhang, Yan; Chen, Chao; et al. (Frontiers in Cell and Developmental Biology, 2025)
AimTo explore the benefits of Morinda officinalis oligosaccharides (MOO) on ischemia-reperfusion (I/R) injury and the possible mechanisms involved.MethodsMyocardial I/R injury were induced by left anterior descending branch ligation. MOO pretreatment was given orally 2 weeks prior to ischemic treatment. Echocardiograms, biochemical parameters, and histological and immunohistochemical analyses were used to determine the benefits of MOO on myocardial I/R injury. Oxidative stress and ferroptosis were examined by biochemical parameters, Western blot, immunohistochemistry, and Tunel staining.ResultsMOO improved cardiac function and reduced myocardial oxidative stress and ferroptosis, which was associated with the inhibition of NADPH Oxidase 4 (NOX4) expression. Whereas, the upregulation of NOX4 abolished the benefits of MOO. Furthermore, MOO enhanced mitochondrial superoxide dismutase 2 (SOD2) activity and stimulated the mitochondrial translocation of glutathione peroxidase 4 (mitoGPX4) by inhibiting NOX4. Mitochondria-specific GPX4 overexpression attenuated mitochondrial oxidative stress and suppressed mitochondria-associated ferroptosis in cardiomyocytes that suffered from hypoxia-reoxygenation (H/R) injury, even after NOX4 overexpression.ConclusionThese results indicate the beneficial effects of MOO on myocardial I/R injury by suppressing oxidative stress and mitochondria-associated ferroptosis through NOX4/mitoGPX4 pathway.